Study on the implementation intention of health protection behavior of college students in epidemic situation of infectious diseases - Ye, He; Mahamed, Mastura; Sha'ri, Sharil Nizam (Redfame Publishing, 2024)
From the perspective of social cognitive theory, this paper refines and integrates the theory of protective motivation, the theory of planned behavior and the individual and social environment factors in risk research, a comprehensive analytical framework was built to predict the implementation intention of public health behaviors. Through the investigation of the college students during the epidemic of Covid-19, we found that the willingness of the public to carry out health behaviors was influenced by two kinds of factors: external social environment and individual internal conditions. As far as the external environment is concerned, perceived normative influence of “Significant others” and informational influence from mass media can positively promote the implementation intention of health protection behavior. At the same time, media attention can also indirectly affect the public's willingness to carry out health behaviors through the mediating effects of self-efficacy and coping efficacy, respectively. As far as internal factors are concerned, self-efficacy is the most powerful direct factor to predict individuals' health behaviors. The existence of cognitive deficit and optimism bias results in the failure of the predictive power of the element of threat assessment on the willingness to carry out health behaviors, however, perceived severity can have a negative effect on health behavior intention through the mediation of the “Avoidance” concept. The study also found that the emotional response not only positively affected the intention to carry out healthy behaviors independently of the cognitive assessment process, but also played a positive moderating role between media attention and the intention to carry out healthy behaviors, however, improper risk concept may have a blocking effect on the implementation intention of health behavior.